Four new species of the genus Phlugiolopsis (Orthoptera: Tettigoniidae: Meconematinae) from Guangxi, China - Pan, Yangyang; Bian, Xun (Zootaxa, 2024)
After examining newly obtained specimens and all the known species from Guangxi, we proposed four new species. They can be distinguished from other species by the male cerci and subgenital plates of both sexes. Based on the specimens deposited in Guangxi Normal University, the illustrations of all new species are provided.